Editor's Note = Note du directeur [22, Fall 1988] - Kealey, Gregory S. (Labour / Le Travail, 1988)
Expresses appreciation to three departing editorial board members, in particular André LeBlanc. Notes the introduction of a new section on access to information and the return of the section on labour accessions at the National Archives. Publication of the updated Canadian labour bibliography is deferred until a later issue. The editor apologizes and notes the correction to be made on p. 145 of Alvin Finkel's article [The Cold War, Alberta Labour, and the Social Credit Regime] in the previous issue.

The Royal Canadian Mounted Police, the Canadian Security Intelligence Service, the Public Archives of Canada, and Access to Information: A Curious Tale - Kealey, Gregory S. (Labour / Le Travail, 1988)
Keywords: Canada; Intelligence service; LABOUR/LE Travail (Book); PUBLIC Archives of Canada; ROYAL Canadian Mounted Police; WORKING papers

Editor's Note = Note du directeur [21, Spring 1988] - Kealey, Gregory S. (Labour / Le Travail, 1988)
The editor reports on the Notebook section introduced in the previous issue as well as the interdisciplinary coverage of labour. The forthcoming issue will launch an annual review of Access to Information legislation, while issue 23 will update on archival and bibliographic resources for the study of labour.

Class, Gender, and Region: Essays in Canadian Historical Sociology - Kealey, Gregory S. (Committee on Canadian Labour History, 1988)
The essays are gathered around two themes: the relationship of sociology and social history, and the intersection of gender, ethnicity, and region with class. Unlike most Canadian essay collections, the contributors and their subjects cover Canada from British Columbia to Newfoundland, with forays into Cape Breton and central Canada. The volume contains articles by Ian McKay, Gordon Darroch, James R. Conley, Alicja Muszynski, Gillian Creese, and Jim Overton. An interesting collection of some of the new work being done in Canada by historians and sociologists, Class, Gender, and Region reflects Charles Tilly’s suggestion that “there should be no disciplinary division of labour: simply both doing social history.” --Publisher's description (Athabasca University Press) Contents: Introduction / Gregory S. Kealey -- The crisis of dependent development: class conflict in the Nova Scotia coalfields, 1872-1876 / Ian McKay --Class in nineteenth-century, central Ontario: a reassessment of the crisis and demise of small producers during early industrialization, 1861-1871 /Gordon Darroch -- “More theory, less fact?” Social reproduction and class conflict in a sociological approach to working-class history / James R. Conley -- Race and gender: structural determinants in the formation of British Columbia’s salmon cannery labour force / Alicja Muszynski -- The politics of dependence: women, work, and unemployment in the Vancouver labour movement before World War II / Gillian Creese -- Public relief and social unrest in Newfoundland in the 1930s: an evaluation of the ideas of Piven and Cloward / James Overton.
Keywords: Historical sociology

Class, Gender, and Region: Essays in Canadian Historical Sociology - Committee on Canadian Labour History; Kealey, Gregory S. (Past CCLH Publications, 1988)
The essays are gathered around two themes: the relationship of sociology and social history, and the intersection of gender, ethnicity, and region with class. Unlike most Canadian essay collections, the contributors and their subjects cover Canada from British Columbia to Newfoundland, with forays into Cape Breton and central Canada. The volume contains articles by Ian McKay, Gordon Darroch, James R. Conley, Alicja Muszynski, Gillian Creese, and Jim Overton. An interesting collection of some of the new work being done in Canada by historians and sociologists, Class, Gender, and Region reflects Charles Tilly's suggestion that "there should be no disciplinary division of labour: simply both doing social history." --Publisher's description
Keywords: Canada; Classes sociales; Conditions sociales; Historical sociology; Regionalism; Régionalisme; Social classes; Social conditions; Sociologie historique

Book Notes [21, Spring 1988] - Palmer, Bryan D.; Kealey, Gregory S. (Labour / Le Travail, 1988)
The article briefly reviews "The Government Generation: Canadian Intellectuals and the State, 1900-1945," by Doug Owram, "Canadian Labour History: Selected Readings," edited by David J. Bercuson, "Rethinking Canada: The Promise of Women's History," edited by Veronica Strong-Boag and Anita Clair Fellman, "First Contract: Women and the Fight to Organize," by Carole Conde and Karl Beveridge, "Will You Have a Union in 1995?" Vector Union Report, edited by Marc Zwelling, "The Guild at Forty: The Struggle Continues," by Roger Stonebanks, "The Canadian Welfare State: Evolution and Transition," edited by Jacqueline S. lsmael, "The Benevolent Slate: The Growth of Welfare in Canada," edited by Allan Moscovitch and Jim Albert, "The Bedroom and The State: The Changing Practices and Politics sf Contraception ana Abortion in Canada, 1880-1980," by Angus McLaren and Arlene Tigar McLaren, "Power and Place: Canadian Urban Development in the North American Context," edited by Gilbert A. Stelter and Alan F. J. Artibise, "Democracy and Capitalism: Properly, Community, and the Contradicttons oo Modern Social Thought," by Samuel Bowles and Herbert Gintis, "A Vision of Unity: History of the Bakery and Confectionery Workers International Union," and "Challenge and Change: History of the Tobacco Workers International Union," by Stuart Bruce Kaufman, "Labor Leaders in America," edited by Melvyn Dubofsky and Warren Van Tine, "Confrontation, Class Consciousness, and the Labor Process: Studies in Proletarian Class Formation," edited by Michael Hanagan and Charles Stephenson, "The Miners' Strike: Loss Without Limit," by Martin Adeney and John Lloyd, "Women and Work in Preindustrial Europe," edited by Barbara Hanawalt, "Collected Essays: v. 1 — Writing and Revolution in 17th Century England; v. 2 — Religion and Politics in 17th Century England; v. 3 — People and Ideas in 17th Century England," by Christopher Hill, "France: Fin de Siècle," by Egen Weber, and "Bailing Out the System: Reformist Socialism in Western Europe, 1944-1985," by Ian Birchall / reviews by Bryan D. Palmer -- "Morning in His Heart: The Life and Writings of Watson Kirkconnell," by J.R.C. Perkin and James B. Snelson / review by Gregory S. Kealey.

On the Job: Confronting the Labour Process in Canada - Heron, Craig; Storey, Robert H.; Steedman, Mercedes; Frank, David; Foster, John Bellamy; Lowe, Graham S.; Reiter, Ester; Radforth, Ian; Strong-Boag, Veronica; Kealey, Gregory S.; Craven, Paul; Traves, Tom; et al. (McGill-Queen's University Press, 1988)
Every day millions of Canadians go out to work. They labour in factories, offices, restaurants, and retail stores, on ships, and deep in mines. And every day millions of other Canadians, mostly women, begin work in their homes, performing the many tasks that ensure the well-being of their families and ultimately, the reproduction of the paid labour force. Yet, for all its undoubted importance, there has been remarkably little systematic research into the past and present dynamics of the world of work in Canada. The essays in this volume enhance our understanding of Canadians on the job. Focusing on specific industries and kinds of work, from logging and longshoring to restaurant work and the needle trades, the contributors consider such issues as job skill, mass production, and the transformation of resource industries. They raise questions about how particular jobs are structured and changed over time, the role of workers' resistance and trade unions in shaping the lives of workers, and the impact of technology. Together these essays clarify a fundamental characteristic shared by all labour processes: they are shaped and conditioned by the social, economic, and political struggles of labour and capital both inside and outside the workplace. They argue that technological change, as well as all the transformations in the workplace, must become a social process that we all control. --Publisher's description